River plume and sediment transport seasonality in a non-tidal semi-enclosed brackish water estuary of the Baltic Sea. (30th October 2020) - Salmela, J.; Kasvi, E.; Alho, P.
Abstract: Our study aims to determine the development of sediment-rich freshwater plumes in a non-tidal brackish water-dominated (salinity < 6) estuary in the Halikonlahti Bay, Northern Baltic Sea. We studied three seasons with different wind conditions and discharges: two open water periods, one with low (~0.2 m³/s) and one with high (31–40 m³/s) river discharges, and one ice-covered period with high (28–40 m³/s) river discharge. To conduct our analyses, we measured suspended sediment concentration (SSC), turbidity, salinity and temperature of bottom and surface waters together with current measurements along the estuary. Water samples were collected with LIMNOS water sampler and current measurements were done with acoustic Doppler current profiler. The results indicate that river plume develops under high river discharge, while during low river discharge the plume is very limited in extent. In open water conditions, SSC increased approximately ten-fold in the estuary head, with increased discharge from 0.2 m³/s to 31 m³/s. Buoyant plumes developed in both open channel and ice-cover conditions during high river discharge periods even in a weakly stratified environment, where the salinity difference was less than five over the entire water column. Unlike salinity, small temperature differences between river and seawater did not contribute the development of buoyant sediment plume. Weak stratification together with reduced wind-induced mixing was found to limit the sediment mixing between fresh surface and saline (~5) bottom layers in both ice-covered and open water conditions. For example, even 2–5 times higher SSCs were found at surface waters compared to bottom waters over a shallow (~4 m) water column. Wind and river discharge induced estuarine currents were found. Inverse estuary circulation developed under the conditions of low river discharge and inshore directed wind. High river discharge together with salinity stratification formed a positive estuarine circulation pattern, with surface outflow and bottom inflow. Highlights: Buoyant river plumes form in both ice-covered and open water conditions. Buoyant river plumes form even in conditions of low salinity stratification. Low salinity stratification reduces sediment mixing within water column. Small water temperature differences do not contribute the behaviour of river plumes.